POLYMORPHISM C634G OF THE VASCULAR ENDOTHELIAL GROWTH FACTOR A GENE IN PATIENTS WITH DIABETIC FOOT IN THE TRANS-BAIKAL TERRITORY - Троицкая, Наталья Игоревна; Шаповалов, Константин Геннадьевич (Medicine in Kuzbass, 2023)
Purpose of the work – to study the frequency of occurrence of genotypes and alleles of the C634G polymorphism of the VEGFA gene in patients with a mixed form of DFS and in the control group living in the Trans-Baikal Territory.Materials and methods. The study involved 199 patients with a mixed form of diabetic foot syndrome and 100 practically healthy people, in whom the frequency of occurrence of genotype variants and the C634G polymorphism alley of the vascular endothelial growth factor A gene was studied by polymerase chain reaction.Results. The G/G genotype was 1.4 times more likely to be registered in the group with the development of diabetic foot syndrome. The frequency of the G/C genotype did not differ in the studied groups of heterozygotes. The C/C genotype in the group of patients was registered 2.9 times less frequently than in the control group. With the development of diabetic foot syndrome, allele G was detected 1.9 times less than in the control group. Allele C in the group of patients was 2.4 times more common than in the control group.Conclusion. The relationship between the variants of the genotypes of the C634G polymorphism of the VEGFA gene and the development of DFS in the population of the Trans-Baikal Territory was revealed.
Keywords: diabetic foot syndrome; gene polymorphism; vascular endothelial growth factor